Development and Challenges of Using Trademark Rights as Intangible Assets in Bankruptcy Assets in Indonesia (Universitas Negeri Semarang, 2022)
Intellectual property rights in the form of trademarks rights are company assets that have economic value. In its development, trademark rights can become part of the debtor’s bankruptcy estate in a bankruptcy. However, in its implementation there are challenges in the use of trademark rights as bankrupt assets in order to pay off the debts of the bankrupt debtor. This study aims to determine the development of the use of trademark rights as bankrupt assets and analyze the challenges of trademarks execution as assets of bankrupt debtors. This research is a normative legal research using a statutory approach and a conceptual approach. The results showed that a trademark as a type of object, related to the bankruptcy process, is a type of object that can be used as part of assets in the process of paying debts to creditors, because intangible assets that have economic value and trademark rights can be transferred handing over their rights to other parties is part of the bankruptcy estate. The challenges faced in the use of trademark rights as bankrupt assets are related to trademark valuation, protection status and the validity period of trademark protection, as well as related to disputes over trademarks with third parties.